Hubungan Sikap dan Konsumsi Junk Food dengan Konsumsi Sayur dan Buah pada Mahasiswa Jurusan Gizi - Kamalia Noor Aziza; Yasir Farhat (Jurnal Riset Pangan dan Gizi, 2021)
Background : The Physiological fulfillment of adolescents requires the fulfillment of adequate nutrition, including fruits and vegetables. However, their current diet has changed. They tend to choose fast food such as junk food which contains added sugar and fat in excessive amounts rather than consuming vegetables, fruit and milk. According to result of basic health research (Riskesdas) in 2018, the proportion of fruit / vegetable consumption per day in a week for people aged 5 years and over, according to the Regency / City of South Kalimantan Province, Banjarbaru City has a level of non-consumption reaching 11,79%, 1-2 portions a week reaching 78,96%, 3-4 servings a week reaches 8,64%, and more than 5 servings a week reaches 0,61%. Objectives : The purpose of this study was to determine the relationship between attitudes and junk food on the level of vegetable and fruit consumption among students majoring in nutrition at the Politeknik Kesehatan Kemenkes Banjarmasin. Methods : This type of research is an analytical observational study with a cross sectional approach. The population of this study were 294 students majoring in nutrition at the Health Polytechnic of the Ministry of Health, Banjarmasin. Sampling used 83 people with simple random sampling technique. This research was conducted using an online questionnaire with WhatsApp and Google Form. Data analysis using the Spearman Rank correlation test α = 0,05. Results : The results showed that the results of the correlation test using the Rank Spearman correlation test found that there was no significant relationship between attitudes and consumption of vegetables and fruits and there is a significant relationship between consumption of junk food and consumption of vegetables and fruit. Conclusions : Students who have low levels of vegetable and fruit consumption are expected to be able to apply the nutritional knowledge that has been learned in their daily life. In addition, they can raise awareness about the importance of eating vegetables and fruit.